Pengaruh Implementasi Manajemen Strategik terhadap Ketahanan Bisnis saat Pandemi Covid-19 pada PT. Es Teh Indonesia Makmur - Sudiro, Allya Nathalie Radina; Ruslim, Herman (https://jurnal.binamandiri.ac.id/, 2023)
The global Covid-19 pandemic, among other industries, has had a considerable impact on the Indonesian franchise business. The franchise PT. Es Teh Indonesia Makmur is one of the companies affected by this pandemic. This study aims to investigate the role that strategic management plays in a company's ability to withstand the Covid-19 pandemic. One of the sampling techniques utilized in the quantitative research method is purposeful sampling. The responders were 50 employees of the PT. Es Teh Indonesia Makmur in Jakarta. The data gathered through questionnaires was examined using multiple linear regression techniques. The results showed that PT. Es Teh Indonesia Makmur's implementation of strategic management considerably increased business resilience in the face of the Covid-19 epidemic. It is intended that the business may maintain and enhance the application of strategic management in order to increase business resilience in the face of the Covid-19 epidemic, it is expected that the company may continue and improve the use of strategic management.